Autologous haematopoietic stem cell transplantation without CD34+ cell selection in refractory Crohn's disease. Issue 2 (25th September 2007) - Cassinotti, A; Annaloro, C; Ardizzone, S; Onida, F; Volpe, A Della; Clerici, M; Usardi, P; Greco, S; Maconi, G; Porro, G Bianchi; Deliliers, G Lambertenghi
Abstract : Objectives: Autologous haematopoietic stem cell transplantation (HSCT) with CD34 + cell selection has recently been used in the treatment of refractory Crohn's disease, showing good safety and promising efficacy. We investigated the safety and efficacy of HSCT with unselected peripheral blood stem cells (PBSCs) in moderate–severe refractory Crohn's disease. Patients: Four patients (three male, one female; age range 26–45 years) with active moderate–severe Crohn's disease (median Crohn's Disease Activity Index (CDAI) 319, range 272–345), refractory or intolerant to multiple drugs including infliximab, were enrolled. Interventions: Unselected PBSCs were collected after mobilisation with cyclophosphamide (CTX) 1.5 g/m2 and granulocyte-colony stimulating factor (G-CSF) 10 μg/kg. The conditioning regimen included CTX 50 mg/kg on days −5 to −2 and rabbit anti-thymocyte globulin (ATG) 2.5 mg/kg on days −4 to −2. Main outcome measures: Primary endpoints were toxicity and clinical remission (CDAI<150) at 3 months. Secondary endpoints were clinical and endoscopic response at 3 months and toxicity, clinical and endoscopic remission at 12 months. Results: No improvement or slight deterioration was observed following mobilisation (median CDAI 339, range 258–404). At the third month, the primary endpoint of clinical remission was achieved in all patients, with a median CDAI of 91 (range 56–102), and complete endoscopic remission was achieved in 2/3 patients. After a median follow-up of 16.5 months, 3/4 patients maintained both clinical and endoscopic remission, despite withdrawal of all drugs, and complete fistula closure was observed in all affected patients. No deaths or life-threatening infection occurred. Unexpected adverse events included a perianal abscess after mobilisation in one patient, pleural and pericardial effusions in another and BK virus-related macrohaematuria in another, all rapidly resolved with conservative treatment. Conclusion: Autologous HSCT with unselected PBSC appears to be safe and can induce and maintain remission in previously refractory Crohn's disease patients.